Using necessary condition analysis to understand digital storytelling’s impact on consumer behavior - Lisboa, A.; Dias, Á.; Abrantes, J. L.; Ferreira, B.; Souca, C. (Journal of Marketing Analytics)
Digitalization disrupted the marketing landscape, enabling connection with stakeholders, but also introducing heightened competition and digitally empowered consumers. These consumers navigate a world of information overload, pushing brands to look for innovative communication strategies to break through the clutter. Brand storytelling emerged as a powerful tool in this regard, engaging consumers through cognitive and emotional pathways. This study explores the necessary conditions for effective digital storytelling campaigns, using two techniques for data analysis. Using narrative transportation theory, and survey consumer data, the research evidences the cognitive path foundational role to convert storytelling to purchase intention. Conversely, the emotional path, while influential for word-of-mouth, is neither a necessary nor a sufficient condition for purchase intention. These findings highlight the strategic value of overall brand equity in storytelling campaigns, offering actionable insights for more effective marketing strategies.